Retrospective surveillance of viable Bacillus cereus group contaminations in commercial food and feed vitamin B2 products sold on the Belgian market using whole-genome sequencing - Bogaerts, Bert; Fraiture, Marie-Alice; Huwaert, Astrid; Van Nieuwenhuysen, Tom; Jacobs, Bram; Van Hoorde, Koenraad; De Keersmaecker, Sigrid C. J.; Roosens, Nancy H. C.; Vanneste, Kevin (Frontiers in Microbiology, 2023)
Bacillus cereus is a spore-forming bacterium that occurs as a contaminant in food and feed, occasionally resulting in food poisoning through the production of various toxins. In this study, we have retrospectively characterized viable B. cereus isolates originating from commercial vitamin feed and food B2 additives collected between 2016 and 2022 by the Belgian Federal Agency for the Safety of the Food Chain from products sold on the Belgian market. In total, 75 collected product samples were cultured on a general medium and, in case of bacterial growth, two isolates per product sample were collected and characterized using whole-genome sequencing (WGS) and subsequently characterized in terms of sequence type (ST), virulence gene profile, antimicrobial resistance (AMR) gene profile, plasmid content, and phylogenomic relationships. Viable B. cereus was identified in 18 of the 75 (24.00%) tested products, resulting in 36 WGS datasets, which were classified into eleven different STs, with ST165 (n=10) and ST32 (n=8) being the most common. All isolates carried multiple genes encoding virulence factors, including cytotoxin K (52.78%) and cereulide (22.22%). Most isolates were predicted to be resistant to beta-lactam antibiotics (100%) and fosfomycin (88.89%), and a subset was predicted to be resistant to streptothricin (30.56%). Phylogenomic analysis revealed that some isolates obtained from different products were closely related or even identical indicating a likely common origin, whereas for some products the two isolates obtained did not show any close relationship to each other or other isolates found in other products. This study reveals that potentially pathogenic and drug-resistant B. cereus can be present in food and feed vitamin B2 additives sold on the Belgian market, indicating the possibility that they could occur in other microbial fermentation products as well, posing a potential public health risk.